2011
DOI: 10.1186/gb-2011-12-2-r20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the social amoebae Dictyostelium discoideum and Dictyostelium purpureum

Abstract: BackgroundThe social amoebae (Dictyostelia) are a diverse group of Amoebozoa that achieve multicellularity by aggregation and undergo morphogenesis into fruiting bodies with terminally differentiated spores and stalk cells. There are four groups of dictyostelids, with the most derived being a group that contains the model species Dictyostelium discoideum.ResultsWe have produced a draft genome sequence of another group dictyostelid, Dictyostelium purpureum, and compare it to the D. discoideum genome. The assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
185
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(189 citation statements)
references
References 115 publications
(128 reference statements)
4
185
0
Order By: Relevance
“…In this analysis, the more social genes had a lower probability of having homologs, an elevated rate of amino acid change, and a lower conservation score, supporting our hypothesis (92). The result could also be attributable to weaker purifying selection on social genes, however, and a better analysis would be between more closely related species.…”
Section: Control Of Conflict By Powersupporting
confidence: 73%
See 1 more Smart Citation
“…In this analysis, the more social genes had a lower probability of having homologs, an elevated rate of amino acid change, and a lower conservation score, supporting our hypothesis (92). The result could also be attributable to weaker purifying selection on social genes, however, and a better analysis would be between more closely related species.…”
Section: Control Of Conflict By Powersupporting
confidence: 73%
“…Our test of this hypothesis used the newly sequenced species D. purpureum and compared it with D. discoideum (92). Unfortunately, this is not an ideal pair of species because their proteins are as diverged as those of humans and fish.…”
Section: Control Of Conflict By Powermentioning
confidence: 99%
“…The first analysis of poly-amino acid stretches in D. discoideum showed that such sequences occur only in specific protein families (62). More recent work by Sucgang et al suggested that poly-amino acid repeats are microsatellites (29). Moreover, these authors provided data that contradict the notion that the N/Q-rich sequences are functional.…”
Section: Discussionmentioning
confidence: 45%
“…Apart from D. discoideum, D. purpureum is the only Dictyostelid whose genome has been sequenced and fully annotated (29). We found ∼900 candidate proteins in the proteome of D. purpureum (Dataset S1).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation